2000
DOI: 10.1046/j.1365-2923.2000.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Task-based learning: the answer to integration and problem-based learning in the clinical years

Abstract: Task-based learning: the answer to integration and problembased learning in the clinical years RM Harden, J Crosby, MH Davis, PW Howie & AD StruthersIntoduction Integrated teaching and problem-based learning (PBL) are powerful educational strategies. Dif®culties arise, however, in their application in the later years of the undergraduate medical curriculum, particularly in clinical attachments. Two solutions have been proposed ± the use of integrated clinical teaching teams and time allocated during the week f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
1
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(89 citation statements)
references
References 16 publications
(16 reference statements)
0
82
1
5
Order By: Relevance
“…TBL was mainly applied in medical education (Harden, Crosby, Davis, & Struthers, 2000;Ozan, Karademir, Gursel, Tanskiran & Musal, 2005), language learning (Gass, Mackey, & Feldman, 2011;Hashemi, Azizinezhad, & Darvishi, 2012) and computer-aid learning (Whittington & Campbell, 1998;Lee & Shin, 2012). But there were few about the TBL applied in chemistry experiment teaching (Zhou et al, 2010c).…”
Section: Task-based Learning In Chemistry Experiments Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…TBL was mainly applied in medical education (Harden, Crosby, Davis, & Struthers, 2000;Ozan, Karademir, Gursel, Tanskiran & Musal, 2005), language learning (Gass, Mackey, & Feldman, 2011;Hashemi, Azizinezhad, & Darvishi, 2012) and computer-aid learning (Whittington & Campbell, 1998;Lee & Shin, 2012). But there were few about the TBL applied in chemistry experiment teaching (Zhou et al, 2010c).…”
Section: Task-based Learning In Chemistry Experiments Teachingmentioning
confidence: 99%
“…Knowledge is constructed through collaboration-interactions among students and between students and teachers, connected by task in TBL (Atwater, 1996). The learning results are not only the tasks but also the concepts and mechanisms underlying the tasks (Harden et al, 2000). Moreover, the cooperation in students is utilized fully and the team spirit is fostered through TBL.…”
Section: Task-based Learning In Chemistry Experiments Teachingmentioning
confidence: 99%
“…10 Tomorrow's doctors also fostered collaboration on national initiatives: an agreed list of essential skills for medical graduates, 11 and essential learning outcomes for Scottish medical undergraduates. 12 Students are more likely to adopt a desirable deep approach to learning when curricula provide opportunities for them to exercise choice in the method and topic of study, but it is too early to evaluate the impact of new 'core and option' curricula on the skills and behaviour of the next generation of UK doctors.…”
Section: Defining a Core Curriculummentioning
confidence: 99%
“…In our study, excellent teaching residents suggested five general themes to adhere by on the wards (Table 3): assuming the role of leader, creating a learning environment, taking advantage of teaching opportunities, empowering learners, and habituating the practice of teaching. Educational research has recognized the value of an instructor acting as a leader and role model in order to establish an effective working and teaching relationship with one's learners (Harden et al 2000). One study involving medical students and residents supported the idea of role modeling as an effective teaching strategy wherein the behaviors of residents were found to be more instructive than a resident simply providing facts on rounds (Wilkerson et al 1986).…”
Section: Discussionmentioning
confidence: 99%